Research lift coefficient on the distance between the revolving cylinders a turbulent stream - Н.К. Танашева; А.Н. Дюсембаева; Н.Н. Шуюшбаева (Қарағанды университетінің хабаршысы. Физика сериясы)
In this paper the possibilities of using a system of revolved cylinders as part of a wind turbine are considered. The aerodynamic forces in the cross-flow of a cylinder and a system of two cylinders have been measured. A method for determining the optimal distance between the cylinders in their cross-flow has been developed. We experimentally determined the conditions under which the Magnus effect contributes to the largest increase of a lift force and, correspondingly, to the increase of the wind turbine efficiency. This can be used to create multi-bladed wind turbines of a new generation based on the Magnus effect. The aerodynamic characteristics of the cylinders with diameters 10 cm in diameter, that is the rotary motion, is determined by the maximum value with the coefficient of lifting force and the frontal impedance coefficient. These results are useful for us in practice, as these results can be used in smaller wind speed engines. In the local economy, the use of local wind power is a convenient, affordable, and environmentally friendly, with a minimal wind speed engine focused on reducing the deficit of electricity, which is one of the key issues in rural areas.